2022
DOI: 10.1021/acs.jafc.2c02115
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Silico Analyses of the Adiponectin Receptor Agonistic Action of Soybean Tripeptides

Abstract: The Tyr-Pro (YP) dipeptide can serve as an adiponectin receptor 1 (AdipoR1) agonist. We thus investigated the AdipoR1-agonistic potential of YP-related tripeptides in the soybean protein sequence. Among the 17 soybean candidate tripeptides, those elongated at the C-terminus of YP (0.1 μM YPG, 140 ± 16%; 0.1 μM YPE, 141 ± 22%; 0.1 μM YPP, 145 ± 19%; 0.1 μM YPQ, 143 ± 20%; p < 0.05) significantly promoted glucose uptake by L6 muscle myotubes, comparable to the effect of 0.1 μM AdipoRon (163 ± 52%, p < 0.05). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…To date, there have been no reports on natural AdipoR1 agonists, except for our previous studies where peptides, including Tyr−Pro, interacted with AdipoR1 in skeletal muscle cell line experiments and by in silico molecular docking simulation analysis. 8,21 Our subsequent studies demonstrated that Tyr−Pro has brain-beneficial effects through intact BBB transport and accumulation in the mouse brain parenchyma 7 and by improving long-term memory impairment in Aβ-induced acute AD mice. 6 In acute AD mouse experiments, we found that a 2 week administration of Tyr−Pro resulted in a significant increase in ChAT expression in the cerebral cortex region.…”
Section: Discussionmentioning
confidence: 95%
“…To date, there have been no reports on natural AdipoR1 agonists, except for our previous studies where peptides, including Tyr−Pro, interacted with AdipoR1 in skeletal muscle cell line experiments and by in silico molecular docking simulation analysis. 8,21 Our subsequent studies demonstrated that Tyr−Pro has brain-beneficial effects through intact BBB transport and accumulation in the mouse brain parenchyma 7 and by improving long-term memory impairment in Aβ-induced acute AD mice. 6 In acute AD mouse experiments, we found that a 2 week administration of Tyr−Pro resulted in a significant increase in ChAT expression in the cerebral cortex region.…”
Section: Discussionmentioning
confidence: 95%
“…The results indicate that all the peptides exhibited stable binding with the bacterial membranes. 23 Interestingly, WT peptide P1 possessed similar affinities toward gram −ve and gram +ve bacterial membranes, as did peptide P3. However, the most interesting observation was the binding affinity of the P2 peptide.…”
Section: Ll-iii Shows Stable Interaction With Membrane Lipids Postmentioning
confidence: 94%
“…The equation used was normalΔ G normalb normali normaln normald = G normalc normalo normalm normalp normall normale normalx ( G m e m b r a n e + G p e p t i d e ) where G complex represents the total free energy of the membrane–peptide complex in the water system, and G membrane and G peptide represent the total free energies of the separated membrane and peptide, respectively. Only the enthalpic components were considered in the computational estimation …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides AdipoRon derivatives, oligopeptides also reveal promising anti-NASH potencies. For instance, tripeptides from soybean activate AdipoR1 and their anti-NASH potencies are expected to be investigated in the future [ 146 ]. Moreover, AdipoR1/AdipoR2 dual agonist JT003 activates both AdipoR1/AdipoR2, as well as AMPK, PPARα, and PI3K-Akt pathways.…”
Section: The Secreted Proteins-receptor Signaling Regulates Nash Prog...mentioning
confidence: 99%